Gambaran tingkat kepuasan pasien terhadap fungsi pengunyahan gigi tiruan jembatan (Kajian pada pasien RSGM-P FKG Universitas Trisakti) - Eka Seftiana Indah Sari; Monica Cecylia Tuela (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Missing a tooth can lead to reduced masticatory efficiency. The solution to this problem is to use a dental bridge. However, based on research conducted by Geiballa, it is known that there are patients who are dissatisfied with the masticatory function of their fixed dentures. Dissatisfaction can have a detrimental effect on patients. So it is necessary to evaluate patient satisfaction, which focuses on masticatory function, to find out more about the patient's opinion on dental bridge treatment. Objectives: To describe the level of satisfaction of dental bridge users with masticatory function at RSGM-P FKG Trisakti University. Methods: This type of research is observational descriptive with a cross-sectional design. The study was conducted on 30 respondents who received dental bridge treatment at the negative room clinic of the RSGM-P FKG Trisakti University using a questionnaire. Results: The results showed that 90% of the patients were satisfied with the masticatory function of the dental bridge. Men who were satisfied were 94.6%, while women were only 84.6%. Based on age category, 100% of patients aged 17-25 years, 46-55 years, and 56-65 years were satisfied, while 81.8% aged 26-35 years and 75% aged 36-45 years. Based on the latest level of education, it is known that 100% of patients with primary education are satisfied, while 92.3% have secondary education, 71.4% have higher education. Conclusion: The majority of patients who receive bridge denture treatment at RSGM-P FKG Trisakti University are satisfied with their masticatory function.